2022
DOI: 10.1021/acs.jpcc.2c04416
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge-Modulated Switchable CO2 Capture on Graphene-like BeN4 with Beryllium Vacancy

Abstract: Beryllonitrene is a new type of Dirac semimetal two-dimensional (2D) material that has recently been fabricated and attracted significant attention with potential for carbon dioxide (CO2)-related applications. The unique symmetric geometry of this material offers different energetically favorable adsorption sites for CO2 uptake. Here, we report that single-vacancy beryllonitrene with a central hollow symmetric atomic ring can be served as a highly efficient CO2 capture adsorbent. Charge modulation response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…For example., Li-doped BeN 4 for the capture of CO 2 was reported by Pu et al The pristine BeN 4 monolayer was incapable of CO 2 capturing due to low adsorption energy, but the Li doping could enhance it [39]. Similarly, Mahmoudi et al also showed that the vacancy created in the BeN 4 monolayer could modulate the CO 2 adsorption capability [40]. The study of ammonia sensing by defective 2D BeN 4 monolayer is unknown to the authors' knowledge.…”
Section: Introductionmentioning
confidence: 97%
“…For example., Li-doped BeN 4 for the capture of CO 2 was reported by Pu et al The pristine BeN 4 monolayer was incapable of CO 2 capturing due to low adsorption energy, but the Li doping could enhance it [39]. Similarly, Mahmoudi et al also showed that the vacancy created in the BeN 4 monolayer could modulate the CO 2 adsorption capability [40]. The study of ammonia sensing by defective 2D BeN 4 monolayer is unknown to the authors' knowledge.…”
Section: Introductionmentioning
confidence: 97%